DAMPAK GEMPA BUMI TERHADAP KELOMPOK MANULA DI KECAMATAN MEUREUDU KABUPATEN PIDIE JAYA - Dani Ansari; Safrida Safrida; Elly Susanti (Jurnal Ilmiah Mahasiswa Pertanian, 2021)
This study aims to determine the impact of the earthquake on the elderly group in Mereudu District, Pidie Jaya Regency. This study uses a descriptive percentage analysis, the objects in this study are all seniors who are in Mereudu District, Pidie Jaya Regency. The scope of this research is limited to the impact of the earthquake on elderly households and external assistance in post-earthquake recovery in Mereudu District, Pidie Jaya Regency. The data used in this study were sourced from primary data obtained by conducting direct interviews with the elderly, and secondary data obtained from libraries, reports and related institutions related to this research.